PROBLEMS DONE BY THE MICRO TEACHING STUDENTS IN TEACHING THE GRAMMAR FOR A COMMUNICATIVE PURPOSE - Saunir Saun (Universitas Negeri Padang, 2015)
The role of grammar cannot be ignored in the language use. The ungrammatical use of language may result in the misunderstanding betrween the speaker (also the writer) and the listener (also the reader) because grammar also determines the meaning of the language used. Considering its important role, the designers of the SMP and SMA curricula still include the grammar as one of the language features in the curricula. Unfortunately, from long observations in many Micro Teaching classes, it has been found that students still do several problems in teaching grammar deviating from the theory. It seems that it is difficult for the students to practice the theory suggested. This paper discusses the problems done by the Micro Teaching students in the Micro Teaching practice of teaching the grammar of English.